Characterization and performance evaluation of white, Silver Bezoar and Black coated type of Black Bengal Goat in Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
The study was undertaken to know the distribution pattern, morphometric characteristics, production and reproduction peculiarities of White, Silver Bezoar and Black coated types of Black Bengal goat in Sylhet, Mymensingh and Bogra region of Bangladesh. Live weight, body measurements, hair diameter and density per unit area were directly obtained from animals. Milk production, life span, number of kidding and other behavioural data (0-5 score) were collected by interviewing farmersThe proportion of White type linearly decreased from east (30% in Sylhet) to west (18% in Bogra) but an erratic fashion was observed in Silver Bezoar type. White type was significantly (p